Combined Heat and Power System Dispatch Considering Heat Transfer Characteristics of Heat Exchangers - Liming ZOU; Xiaoyan BIAN; Jianjie JIANG; Henchao WU (Zhongguo dianli)
The heat transfer characteristic of heat exchangers is one of the key factors affecting the optimal dispatch of combined heat and power systems. In order to optimize the dispatch of the combined heat and power systems, a three-stage heat transfer model of the extraction steam is established based on the heat transfer principle to describe the heat transfer process of the heat exchanger, and the iteration method is used to calculate the extraction steam under a certain heat load. And then, a joint dispatch model of cogeneration power, thermal power and wind power is proposed with consideration of the heat transfer characteristics of the heat exchangers. Finally, with the minimum coal consumption as the optimization goal, an analysis is made of the influence of the heat exchanger’s heat transfer characteristics on the steam extraction heat transfer process and the combined heat and power system dispatch results. The case study shows that increasing the heat transfer area of the heat exchanger and reducing the water temperature at the outlet of the heat exchanger can improve the wind power consumption capacity to different degrees, and reduce the operating cost. The research results of this paper can provide heat transfer parameters for optimizing the dispatch scheme of the combined heat and power systems.